Genome‐wide loss of CHH methylation with limited transcriptome changes in Setaria viridis DOMAINS REARRANGED METHYLTRANSFERASE (DRM) mutants. (6th May 2022) - Read, Andrew; Weiss, Trevor; Crisp, Peter A.; Liang, Zhikai; Noshay, Jaclyn; Menard, Claire C.; Wang, Chunfang; Song, Meredith; Hirsch, Candice N.; Springer, Nathan M.; Zhang, Feng
SUMMARY: The DOMAINS REARRANGED METHYLTRANSFERASEs (DRMs) are crucial for RNA‐directed DNA methylation (RdDM) in plant species. Setaria viridis is a model monocot species with a relatively compact genome that has limited transposable element (TE) content. CRISPR‐based genome editing approaches were used to create loss‐of‐function alleles for the two putative functional DRM genes in S . viridis to probe the role of RdDM. Double mutant ( drm1ab) plants exhibit some morphological abnormalities but are fully viable. Whole‐genome methylation profiling provided evidence for the widespread loss of methylation in CHH sequence contexts, particularly in regions with high CHH methylation in wild‐type plants. Evidence was also found for the locus‐specific loss of CG and CHG methylation, even in some regions that lack CHH methylation. Transcriptome profiling identified genes with altered expression in the drm1ab mutants. However, the majority of genes with high levels of CHH methylation directly surrounding the transcription start site or in nearby promoter regions in wild‐type plants do not have altered expression in the drm1ab mutant, even when this methylation is lost, suggesting limited regulation of gene expression by RdDM. Detailed analysis of the expression of TEs identified several transposons that are transcriptionally activated in drm1ab mutants. These transposons are likely to require active RdDM for the maintenance of transcriptional repression. Significance Statement: Methylation profiling of Setaria viridis plants that lack functional DOMAINS REARRANGED METHYLTRANSFERASE genes reveal widespread loss of DNA methylation in the CHH sequence context. Transcriptome analysis reveals a small set of genes and transposons that are silenced by RNA‐directed DNA methylation.